EFFECT OF OWNERSHIP STRUCTURE TO DIVIDEND POLICY IN COMPANIES IN INDONESIA - Farah Margaretha (Universitas Trisakti, 2014)
The purpose of this study is to analyze the effect of ownership structure on dividend payout policy in companies listed in Indonesia Stock Exchange. In this study, there are 4 kinds of ownership structures that will be discussed, namely private ownership structure, government ownership structure, foreign ownerships structure and family ownership structure. Dividend payout policy uses DividndPayout Ratio (DPR) indicator Population of this study is all the companies listed in Indonesia Stock Exchange (IDX) 009-2011. Total samples in this study are 85 companies listed in Indonesia Stock Exchange determined by purposive sampling. Based on the study results, from the four ownership structures, only the private ownership structure influence Parliament. The implication for investors in doing this research, the investor can choose the private ownership structure of companies. for financial managers, this study provides information specifically on private companies that one way the companies reduce the agency problem could use dividend payout policy